Effect of Immune Serum or Polymyxin B on Escherichia coli-Induced Inflammation and Vascular Injury - Issekutz, Andrew C. (American Society for Microbiology (ASM), 1982)
Bacterial invasion of the tissues often stimulates a vigorous inflammatory reaction, which may limit the spread of microorganisms but may also be accompanied by serious vascular injury and tissue damage. We previously studied the inflammatory reaction induced by the injection of killed Escherichia coli into rabbit skin, a model suitable for the quantitation of various parameters of inflammation. Here we report the effect of immune serum treatment of the E. coli on their capacity to induce inflammation and vascular injury. Injection of killed E. coli treated with immune serum elicited a reaction which had a smaller increase in vascular permeability (protein exudation), measured with (125)I-labeled albumin, less increase in blood flow, measured with (86)RbCl, less leukocyte infiltration, measured with (51)Cr-labeled leukocytes, and a lesser degree of hemorrhage, measured with (59)Fe-labeled erythrocytes, than E. coli treated with nonimmune serum. Crossover experiments with four different E. coli serotypes and four different antisera indicated that antibody to specific O antigens or a related antigen, but not to K or H antigen, was important for modifying the inflammatory response. Treatment of four different E. coli serotypes with antiserum to “core” glycolipid, produced by immunization with the E. coli J5 mutant, inhibited the inflammatory response to all four E. coli serotypes. Finally, treatment of killed E. coli with polymyxin B also inhibited their inflammation-inducing potential. These results suggest that it may be possible to diminish the magnitude of local vascular and tissue injury associated with E. coli infections by the use of antisera or polymyxin B, which bind to endotoxin on the E. coli.